Inertial parameters for a human body biomechanical modelling - V.M. Soto; M. Gutiérrez (Asociación Española de Ciencias del Deporte, 2010)
This work gives a general view of the inertial parameters needed for the biomechanical modelling of the human body from the biomechanical point of view, making an analysis of the past, present situations and future tendencies in this subject. Human body modelling needs to determine several anatomical points and interconnected segments, which should be complemented with inertial information such as the segmentary mass, centre of gravity position vector, axes of the local segmentary reference system, and also the moments of inertia. The process of obtaining this inertial parameters is essential for biomechanical analysis since it enables us to obtain several basic variables needed in any quantitative analysis of movement, for example the centre of gravity (CG) both segmentary and corporal, the moment of inertia (I) and the segmentary and corporal angular momentum (H). KEY WORDS: Biomechanicals, inertial parameters.